Late Payment Fines for buying and Selling Using Shoppe Pay Latter in Sharia and Legal Studies - Yuswalina, Yuswalina; Imron, Zuhdi (Universitas Islam Negeri Raden Fatah Palembang, 2023)
One of them is business activity using internet media that serves non-cash online buying & selling which’s offered by Shopee, namely Shopee Pay Later. Formulation of the problem: (1) What is the process for implementing fines for late payments for buying & selling using Shopee Pay Later according to Civil Law? (2) What are the fines for delays in buying & selling using Shopee Pay Later according to Fiqh Muamalah? This research is Normative Judicial research. From the results of the study it can be concluded that late payment for buying & selling using Shopee Pay Later will incur a fine of 5% of the total invoice. According to Civil Law, the issuance of fines is permissible because this’s regulated in Article 1243 Paragraph 1 of the Civil Code. Meanwhile, the provision of fines for delays in payment of purchases using Shopee Pay Later according to Fiqh Muamalah, there’re 2 opinions of scholars who’re contradictory. Opinion of scholars who support the awarding of fines, there’is no delay in the next payment. Meanwhile, other scholars don’t support, that late payment fines are included in the category of jahiliyah riba.